Developmental effect of RASopathy mutations on neuronal network activity on a chip - Weiss, Eva-Maria; Guhathakurta, Debarpan; Petrušková, Aneta; Hundrup, Verena; Zenker, Martin; Fejtová, Anna (Frontiers in Cellular Neuroscience, 2024)
RASopathies are a group of genetic disorders caused by mutations in genes encoding components and regulators of the RAS/MAPK signaling pathway, resulting in overactivation of signaling. RASopathy patients exhibit distinctive facial features, cardiopathies, growth and skeletal abnormalities, and varying degrees of neurocognitive impairments including neurodevelopmental delay, intellectual disabilities, or attention deficits. At present, it is unclear how RASopathy mutations cause neurocognitive impairment and what their neuron-specific cellular and network phenotypes are. Here, we investigated the effect of RASopathy mutations on the establishment and functional maturation of neuronal networks. We isolated cortical neurons from RASopathy mouse models, cultured them on multielectrode arrays and performed longitudinal recordings of spontaneous activity in developing networks as well as recordings of evoked responses in mature neurons. To facilitate the analysis of large and complex data sets resulting from long-term multielectrode recordings, we developed MATLAB-based tools for data processing, analysis, and statistical evaluation. Longitudinal analysis of spontaneous network activity revealed a convergent developmental phenotype in neurons carrying the gain-of-function Noonan syndrome-related mutations Ptpn11D61Y and KrasV14l. The phenotype was more pronounced at the earlier time points and faded out over time, suggesting the emergence of compensatory mechanisms during network maturation. Nevertheless, persistent differences in excitatory/inhibitory balance and network excitability were observed in mature networks. This study improves the understanding of the complex relationship between genetic mutations and clinical manifestations in RASopathies by adding insights into functional network processes as an additional piece of the puzzle.
CRIS-Team Scopus Importer:2024-06-28
Keywords: excitation/inhibition balance; mouse models; multielectrode array; network establishment and maturation; neurodevelopmental disorder; Noonan syndrome; principal component analysis; rare diseases

Development and Application of Automatized Routines for Optical Analysis of Synaptic Activity Evoked by Chemical and Electrical Stimulation. - Fejtová, Anna; Guhathakurta, Debarpan; Akdas, Enes Yagiz; Weiss, Eva-Maria (Frontiers in Bioinformatics, 2022)
The recent development of cellular imaging techniques and the application of genetically encoded sensors of neuronal activity led to significant methodological progress in neurobiological studies. These methods often result in complex and large data sets consisting of image stacks or sets of multichannel fluorescent images. The detection of synapses, visualized by fluorescence labeling, is one major challenge in the analysis of these datasets, due to variations in synapse shape, size, and fluorescence intensity across the images. For their detection, most labs use manual or semi-manual techniques that are time-consuming and error-prone. We developed SynEdgeWs, a MATLAB-based segmentation algorithm that combines the application of an edge filter, morphological operators, and marker-controlled watershed segmentation. SynEdgeWs does not need training data and works with low user intervention. It was superior to methods based on cutoff thresholds and local maximum guided approaches in a realistic set of data. We implemented SynEdgeWs in two automatized routines that allow accurate, direct, and unbiased identification of fluorescently labeled synaptic puncta and their consecutive analysis. SynEval routine enables the analysis of three-channel images, and ImgSegRout routine processes image stacks. We tested the feasibility of ImgSegRout on a realistic live-cell imaging data set from experiments designed to monitor neurotransmitter release using synaptic phluorins. Finally, we applied SynEval to compare synaptic vesicle recycling evoked by electrical field stimulation and chemical depolarization in dissociated cortical cultures. Our data indicate that while the proportion of active synapses does not differ between stimulation modes, significantly more vesicles are mobilized upon chemical depolarization.
EVALuna2:523130

Hydroxynorketamine, but not ketamine, acts via α7 nicotinic acetylcholine receptor to control presynaptic function and gene expression - Guhathakurta, Debarpan; Petrušková, Aneta; Akdas, Enes Yagiz; Perelló Amorós, Bartomeu; Frischknecht, Renato; Anni, Daniela; Weiss, Eva-Maria; Walter, Martin; Fejtová, Anna (Translational Psychiatry, 2024)
Ketamine is clinically used fast-acting antidepressant. Its metabolite hydroxynorketamine (HNK) shows a robust antidepressant effect in animal studies. It is unclear, how these chemically distinct compounds converge on similar neuronal effects. While KET acts mostly as N-methyl-d-aspartate receptor (NMDAR) antagonist, the molecular target of HNK remains enigmatic. Here, we show that KET and HNK converge on rapid inhibition of glutamate release by reducing the release competence of synaptic vesicles and induce nuclear translocation of pCREB that controls expression of neuroplasticity genes connected to KET- and HNK-mediated antidepressant action. Ro25-6981, a selective antagonist of GluN2B, mimics effect of KET indicating that GluN2B-containing NMDAR might mediate the presynaptic effect of KET. Selective antagonist of α7 nicotinic acetylcholine receptors (α7nAChRs) or genetic deletion of Chrna7, its pore-forming subunit, fully abolishes HNK-induced synaptic and nuclear regulations, but leaves KET-dependent cellular effects unaffected. Thus, KET or HNK-induced modulation of synaptic transmission and nuclear translocation of pCREB can be mediated by selective signaling via NMDAR or α7nAChRs, respectively. Due to the rapid metabolism of KET to HNK, it is conceivable that subsequent modulation of glutamatergic and cholinergic neurotransmission affects circuits in a cell-type-specific manner and contributes to the therapeutic potency of KET. This finding promotes further exploration of new combined medications for mood disorders.
CRIS-Team Scopus Importer:2024-01-26

P22-2-jD Mit hydrostatischem Hochdruck generierte Ganzzell- Tumorvakzine erzeugen in Kombination mit Strahlentherapie ein immunogenes Tumor-Mikromilieu - Rückert, Michael; Seitz, Christoph; Deloch, Lisa; Weiss, Eva-Maria; Utz, S; Izydor, Marika; Ebel, Nina; Schlücker, Eberhard; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2019)

Rasopathy-Associated Mutation Ptpn11D61Y has Age-Dependent Effect on Synaptic Vesicle Recycling - Guhathakurta, Debarpan; Selzam, Franziska; Petrušková, Aneta; Weiss, Eva-Maria; Akdas, Enes Yagiz; Montenegro-Venegas, Carolina; Zenker, Martin; Fejtová, Anna (Cellular and Molecular Neurobiology, 2024)
Rasopathies are genetic disorders often associated with developmental delay and intellectual disability. Noonan syndrome (NS) is one of the most common Rasopathies, caused by mutations in PTPN11 in more than 50% of cases. In mammalian neurons, PTPN11 controls the trafficking of postsynaptic glutamate receptors. This process is disrupted in neurons expressing PTPN11 variants associated with Rasopathies and is thought to contribute to the cognitive impairments in Noonan syndrome. Recent work revealed presynaptic impairments upon expression of RASopathy-linked PTPN11 variants in Drosophila. However, the presynaptic role of PTPN11 has not yet been addressed in mammals. Here, we investigated membrane trafficking of synaptic vesicles in cultured mouse cortical neurons expressing Rasopathy-associated PTPN11D61Y variant. We observed a significantly smaller readily releasable and total recycling pool of synaptic vesicles. The drop in synaptic vesicle release competence was accompanied by a decreased rate of SV retrieval. Interestingly, the presynaptic phenotype was evident in mature (DIV21) but not in immature (DIV12) neurons. Thus, our data reveal importance of balanced PTPN11 activity for normal trafficking of neurotransmitter-filled synaptic vesicles in the presynaptic ending of mature neurons.
CRIS-Team Scopus Importer:2024-11-29